2014
DOI: 10.1002/tox.22061
|View full text |Cite
|
Sign up to set email alerts
|

Semiquinone glucoside derivative provides protection against γ-radiation by modulation of immune response in murine model

Abstract: Present study was undertaken to evaluate radioprotective and immunomodulatory activities of a novel semiquinone glucoside derivative (SQGD) isolated from Bacillus sp. INM-1 in C57 BL/6 mice. Whole body survival study was performed to evaluate in vivo radioprotective efficacy of SQGD. To observe effect of SQGD on immunostimulation, Circulatory cytokine (i.e., interleukin-2 (IL-2), IFN-γ, IL-10, granulocyte colony stimulating factor (G-CSF), granulocyte macrophage colony stimulating factor (GM-CSF), and macropha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…5,11,19,21 Irradiated macrophages showed suppression of IL‐12 levels at all tested time‐points (except 2 hours; Figure E). Moreover, previous reports have indicated that dwindling IL‐12 levels cause declined stimulation of IFN‐γ by Th 1 cells . On the contrary, NATG pretreatment to irradiated cells revealed a significant ( P < .05) upsurge in IL‐12 levels at all tested time‐points (except 2 hours) clearly suggesting a role of NATG in Th 1 immune response stimulation via IL‐12 pathway …”
Section: Discussionmentioning
confidence: 70%
See 4 more Smart Citations
“…5,11,19,21 Irradiated macrophages showed suppression of IL‐12 levels at all tested time‐points (except 2 hours; Figure E). Moreover, previous reports have indicated that dwindling IL‐12 levels cause declined stimulation of IFN‐γ by Th 1 cells . On the contrary, NATG pretreatment to irradiated cells revealed a significant ( P < .05) upsurge in IL‐12 levels at all tested time‐points (except 2 hours) clearly suggesting a role of NATG in Th 1 immune response stimulation via IL‐12 pathway …”
Section: Discussionmentioning
confidence: 70%
“…Radiation exposure resulted in significant increase in cellular IL‐10 expression (Figure C) that may lead to immune suppression due to its Th 1 cytokines down regulating activities and macrophage costimulatory molecule expression that caused inhibition of antigen presentation and cytokine secretion activity by macrophages . On the contrary, NATG pre‐treatment proficiently neutralized radiation‐induced upsurge in IL‐10 expression at all tested time‐points (Figure C) and thus, it may contribute to maintain immune response by stimulating Th 1 pathway.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations